Огляд сучасних підходів до багатофакторного оцінювання професійного вигорання - Чигрин, Д. Р. (ХНУРЕ, 2024)
This study delves into the existing methodologies and approaches used for the estimation of professional burnout. At present, the topic of professional burnout is gaining considerable attention, due to its wide-ranging impacts on the individual's mental and physical health, as well as organizational productivity. This paper provides a comprehensive overview of current methods and approaches used to measure and assess professional burnout in various work environments. Moreover, a classification of prevalent estimation tools and approaches is provided, to illustrate the variation and scope of current practices in the field. This discussion serves to highlight the strengths and shortcomings of different estimation strategies, thereby paving the way for the development of more effective diagnostic and management solutions for professional burnout.
Keywords: професійне вигорання; втома; багатофакторне оцінювання